ANALYZING FACTORS INFLUENCING ACCOUNTING APPLICATION ADOPTION AMONG F&B MSMES IN WEST JAVA USING THE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY MODEL - Agatha Dwi P. Tambunan, Naomi
MSMEs play a significant role in helping Indonesia achieve stable and sustainable economic growth. Despite the importance of MSMEs to the country's economy, many of them are still struggling for various reasons. One of them is capital limitations. Accounting applications are believed to help enhance MSMEs’ financial management capacity and strengthen access to capital. Unfortunately, the preliminary study conducted by the researcher found that only a few MSMEs have used accounting applications, despite knowing their benefits and the existence of numerous free accounting applications available on the market. This research aims to identify the factors influencing culinary MSMEs' adoption of accounting applications from the perspective of the Unified Theory of Acceptance and Use of Technology (UTAUT) model. According to UTAUT, behavioral intention to adopt a system is affected by performance expectancy, effort expectancy, social influence, and facilitating conditions, while actual use of the system is affected by facilitating conditions and behavioral intention. The data was collected through the quantitative method, where online and offline questionnaires were distributed to owners or managers of culinary MSMEs in West Java. The 246 questionnaire results were then assessed using the PLS-SEM method. The analysis result demonstrated that MSMEs’ behavioral intentions to utilize accounting applications were only positively influenced by performance expectancy, effort expectancy, and facilitating conditions. Additionally, actual usage of the application was affected by behavioral intention and MSMEs’ facilitating conditions. Therefore, accounting application developers are recommended to utilize these factors to enhance adoption of the applications by increasing the application’s performance and usage simplicity. Additionally, the government is also advised to strengthen the facilitating conditions by enhancing digital infrastructure in underserved regions to ensure equitable technology access. In consideration of the study's limitations, future studies may include a more diverse sample of MSMEs from various regions in West Java.